2016
DOI: 10.31768/2312-8852.2016.38(2):80-83
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Sodium Dichloroacetate Against Glioma С6 Depends on Administration Schedule and Dosage

Abstract: Background: Anticancer action of sodium dichloroacetate (DCA) could be related to its ability to activate oxidative phosphorylation leading to enhanced generation of reactive oxygen species and induction of apoptosis. On the other hand, activation of oxidative phosphorylation could promote tumor cell survival, in particular, via increased ATP synthesis. Such ambiguous effects of DCA could influence its anticancer effectiveness, depending on biological properties of a tumor, schedule of DCA administration and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
(11 reference statements)
1
7
0
Order By: Relevance
“…Analysis of the viability parameters in both the DCA-treated PDAC cell lines unveiled a limited percentage of apoptotic/necrotic cells, thereby suggesting a cytostatic rather than a cytotoxic effect exerted by the drug, confirming previous reports [36,37].…”
Section: Discussionsupporting
confidence: 86%
“…Analysis of the viability parameters in both the DCA-treated PDAC cell lines unveiled a limited percentage of apoptotic/necrotic cells, thereby suggesting a cytostatic rather than a cytotoxic effect exerted by the drug, confirming previous reports [36,37].…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, HIF-1 and its mediated metabolic pathways may be promising targets for treating GBM (125). Drugs such as DCA, and IMQ are effective in inhibiting HIF-1 expression and its activity and thus block tumor growth (73,76). Drugs targeting metabolic enzymes downstream of HIF-1 are also effective inhibitors of GBM progression.…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer action of sodium dichloroacetate (DCA) caused ambiguous effects varying from tumor growth stimulation to significant anticancer activity. Under hypoxic conditions, the anticancer efficacy of DCA against glioma С6 cells was significantly enhanced (76). DCA was found to inhibit the glycolytic pathway through glycolytic inhibition which in turn diminished acid production.…”
Section: Regulation Of Glycolysis and Glucose Metabolismmentioning
confidence: 99%
“…Observations were made on GBM cell lines in vitro and in vivo using a rat model [173]. DCA is a drug that has been mainly used in the treatment of metabolic disorders for many years, but recently its antitumor properties have been studied, also regarding gliomas [174][175][176]. Kolesnik et al, showed that DCA and metformin combined therapy is more effective in reducing the viability of cancer cells by about 40% compared to monotherapy.…”
Section: Impact Of Metformin On Treatment Sensitivitymentioning
confidence: 99%